Pengaruh Terapi Bermain (Berdongeng) Terhadap Perkembangan Bahasa Pada Anak Usia Prasekolah (3 - - Hotimah, Husnul; Sunarto, Muhamad; Pratama, Edy A Surya (Universitas Qamarul Huda Badaruddin, 2018)
Language is a communication system that is used voluntarily and socially agreed upon, by using certain symbols to convey and receive messages from one person to another. One delay that can occur in children is the delay in language development. One stimulus that parents can give to improve children's language development is by telling stories. The purpose of this study was to determine the effect of play therapy (storytelling) on ??language development in preschool children (3- <6 years). The design of this study is an experimental research pre test and post test with a quantitative research approach. This study involved two groups, namely the experimental group and the control group. the sample was all preschool children enrolled in PAUD Ukuwah Islamiah Penujak Village who had language problems. The sampling technique in this study was total sampling with 40 respondents. The results of statistical tests based obtained t value of 2.137 with t table of 1.684 and p value = 0.039 which means the value of t> t table value or p value <? so it can be concluded that there is a significant change in language development in preschool children after playing therapy (storytelling). Key words: language development, storytelling therapy